2014
DOI: 10.1590/2176-9451.19.4.058-065.oar
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal maturation in individuals with Down's syndrome: Comparison between PGS curve, cervical vertebrae and bones of the hand and wrist

Abstract: IntroductionThis study was conducted with the aim of adapting the methods developed by Martins and Sakima to assess skeletal maturation by cervical vertebrae in the pubertal growth spurt (PGS) curve. It also aimed to test the reliability and agreement between those methods and the method of hand and wrist radiograph when compared two by two and all together.MethodsThe sample comprised 72 radiographs, with 36 lateral radiographs of the head and 36 hand-wrist radiographs of 36 subjects with Down's syndrome (DS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…This rapid pubertal growth period has been associated with the CVMI stages (Carinhena et al. ; Shapland & Lewis, ). During the pubertal growth spurt, vertebral bodies of males became significantly larger than those of females (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This rapid pubertal growth period has been associated with the CVMI stages (Carinhena et al. ; Shapland & Lewis, ). During the pubertal growth spurt, vertebral bodies of males became significantly larger than those of females (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…; Carinhena et al. ). Although CVMI is commonly used by orthodontists to identify biological age, some researchers question its value in assessing skeletal maturity due to the poor reliability between researchers in visually classifying shape to the same CVMI stage (Nestman et al.…”
Section: Introductionmentioning
confidence: 98%
“…Down syndrome is one of the most common causes of skeletal retardation. 21 In their research, AbouHala et al 1 show that there is a closer value and a smaller difference between dental and chronological age compared to skeletal and chronological age in Down syndrome individuals. It can therefore be said that establishing age by means of the Nolla method is more accurate than using the Greulich and Pyle method in determining skeletal and chronological age.…”
Section: 20mentioning
confidence: 94%
“…10 Research by Carinhena et al, 21 into skeletal age comparing the CVM method and analysis of the palms and wrists in the pubertal growth spurt curve of Down's individual syndrome confirmed that both analyzes produce similar results. Few studies are known to link dental age assessment through the stage of dental calcification with skeletal age determined by CVM.…”
mentioning
confidence: 90%
“…The morphological changes of the cervical vertebral bodies to qualitatively assess skeletal maturation within clinical settings entail the use of a classification index, the Cervical Vertebral Maturation Index (CVMI) (Byrd & Comiskey, 2007; Hassel & Farman, 1995; Lamparski, 1972; Nestman et al, 2011; Pichai et al, 2014; San Román, Palma, Oteo, & Nevado, 2002; Santiago et al, 2012; Yang, Lee, Kim, Cho, & Park, 2014). CVMI uses six stages that capture the morphological changes between ages 6 to 18 years where, in the midsagittal plane, the vertebral bodies transition in shape from an anterior wedge to a horizontal rectangle, then to a square, and finally to a vertical rectangle (Carinhena, Siqueira, & Sannomiya, 2014; Hassel & Farman, 1995; Jaqueira, Armond, Pereira, Alcantara, & Marques, 2010; San Román et al, 2002; Santiago et al, 2012). While these shape changes are apparent in the morphological development of the cervical vertebral bodies, CVMI stages have been questioned due to poor reproducibility (Gray, Bennani, Kieser, & Farella, 2016; Johnson et al, 2016; Nestman et al, 2011; Santiago et al, 2012; Yang et al, 2014) and a low improvement over using chronological age (Chatzigianni & Halazonetis, 2009).…”
Section: Introductionmentioning
confidence: 99%